A comparative study of efficacy of epidural versus interpleural bupivacaine for post operative analgesia after open cholecystectomy - Yadav, RK; Majhi, PC (Journal of College of Medical Sciences-Nepal, 2014)
Background The conventional methods of administering the prescribed doses of intramuscular or intravenous analgesics at fixed time intervals results in widely fluctuating and inadequate plasma level leads to poor post operative pain relief. Despite all advances made in the field of medicine, this symptom called “Pain” has not been combated well. Objective The present study was carried out to compare the efficacy of epidural verses interpleural administration of bupivacaine(0.5%) with adrenaline for post operative pain relieve in patients undergoing open cholecystectomy. Methods We prospectively randomized and compared the post operative pain relieve with the reference of visual analog score (VAS) in patients undergoing elective open cholecystectomy in college of medical sciences-teaching hospital, Bharatpur, Chitwan. Forty adult patients undergoing elective cholecystectomy were divided into two groups. Twenty patients in each group were subjected to a different technique of post-operative analgesia, namely thoracic epidural and interpleural instillation of 0.5% bupivacaine. These two groups were then compared in relation to changes produced in the pain scores, vital parameters and complication and side effects associated with the two techniques. The study was conducted for 24 hour postoperatively. Observation: Both thoracic epidural and interpleural instillation of 0.5% bupivacaine compared favorably with regard to analgesia in the present study. In general, the pain relief following thoracic epidural was more complete compared to interpleural but this was not clinically significant. Conclusion The present study shows that both the techniques are equally effective in providing analgesia following cholecystectomy. However, neither technique rendered the patients completely pain free at all times during first 24 hours. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-4, 15-23 DOI: http://dx.doi.org/10.3126/jcmsn.v9i4.10232